Cholecystitis: association between ultrasound findings and surgical outcomes. Issue 5 (May 2022) - Van Roekel, D.; LeBedis, C.A.; Santos, J.; Paul, D.; Qureshi, M.M.; Kasotakis, G.; Gupta, A.
Abstract : AIM: To identify sonographic signs of cholecystitis that correlate with surgical outcomes. MATERIALS AND METHODS: Three hundred and thirty-three consecutive patients who underwent cholecystectomy between 22/06/2014 and 1/3/2016 and underwent abdominal ultrasound (US) within 7 days of surgery were included. Individual US signs, including gallstones, gallbladder distention, wall thickening, pericholecystic fluid, and abscess, were graded by two radiologists, 1 and 2. Outcomes included operative duration (OD), drain placement, partial cholecystectomy, conversion from laparoscopic to open cholecystectomy, surgical pathology, bile leak, infection, and 30-day readmission. US signs and outcomes were analysed using analysis of variance, chi-square test, or odds ratios (OR). RESULTS: Radiologist 1 reported 141/333 and radiologist 2 reported 128/333 patients showed gallbladder distention. For the subset with OD, radiologist 1 reported 140/320 and radiologist 2 reported 126/320 patients showed gallbladder distention. Distention was predictive of increased OD (radiologist 1, +23.2 minutes, p< 0.0001; radiologist 2, +19.4 minutes, p= 0.0003). Cases with gallbladder distention were more likely to have surgical drain placement (OR= 2.60; 95% confidence interval [CI]: 1.12–6.08, p= 0.027 radiologist 1; OR=2.59; 95% CI: 1.13–5.95, p= 0.025 radiologist 2). Wall thickening was present in 126/333 patients reported by radiologist 1 and 120/333 by radiologist 2. Cases with wall thickening were more likely to have drain placement (OR=2.66; 95% CI: 1.16–6.13, p= 0.021 radiologist 1; OR=3.49; 95% CI: 1.49–8.16, p= 0.004 radiologist 2). For the subset with OD, wall thickening was present for 121/320 reported by radiologist 1 and 116/320 by radiologist 2 and predicted longer OD (radiologist 1, +15.9 minutes, p= 0.0033; radiologist 2, +13.3 minutes, p= 0.0143). CONCLUSION: Gallbladder distention and wall thickening on US correlate with prolonged OD and surgical drain placement in patients with cholecystitis. Highlights: US finding of gallbladder wall thickening is associated with a longer operative time. US finding of gallbladder distension is associated with a longer operative time. Gallbladder wall thickening is associated with increased odds of drain placement. US finding of gallbladder wall thickening may help anticipate a longer operative time. US finding of gallbladder distension may help anticipate a longer operative time.